Impact of a culturally tailored parenting programme on the mental health of Somali parents and children living in Sweden: a longitudinal cohort study - Marie Klingberg-Allvin; Raziye Salari; Fatumo Osman; Ulla-Karin Schön; Renée Flacking; Linda Vixner (BMJ Open)
Objectives This study aimed to evaluate the long-term impact (3-year follow-up) of a culturally tailored parenting support programme (Ladnaan) on the mental health of Somali-born parents and their children living in Sweden.Methods In this longitudinal cohort study, Somali-born parents with children aged 11–16 were followed up 3 years after they had participated in the Ladnaan intervention. The Ladnaan intervention comprises two main components: societal information and the Connect parenting programme delivered using a culturally sensitive approach. It consists of 12 weekly group-based sessions each lasting 1–2 hours. The primary outcome was improved mental health in children, as measured by the Child Behaviour Checklist (CBCL). The secondary outcome was improved mental health in parents, as measured by the General Health Questionnaire-12. Data were collected from the parent’s perspective.Results Of the 60 parents who were originally offered the intervention, 51 were included in this long-term follow-up. The one-way repeated measures (baseline to the 3-year follow-up) analysis of variance for the CBCL confirmed maintenance of all the treatment gains for children: total problem scores (95% CI 11.49 to 18.00, d=1.57), and externalising problems (95% CI 2.48 to 5.83, d=0.86). Similar results were observed for the parents’ mental health (95% CI 0.40 to 3.11, d=0.46).Conclusion Positive changes in the mental health of Somali-born parents and their children were maintained 3 years after they had participated in a parenting support programme that was culturally tailored and specifically designed to address their needs. Our findings highlight the long-term potential benefits of these programmes in tackling mental health issues in immigrant families.Trial registration number NCT02114593.